Survivability and metabolic activity of Lactobacillus casei 01 incorporating lychee juice plus inulin under simulated gastrointestinal environment - N. Kingwatee (2018)
A study of survivability of Lactobacillus casei 01 in simulated gastrointestinal environment under three treatment conditions i.e. L. casei 01 plus lychee juice, L. casei 01 plus lychee juice plus 3% inulin and L. casei 01 plus lychee juice plus 5% inulin was investigated, while the control, L. casei 01 in the colon fluid also run simultaneously. It was found that L. casei 01 combined with lychee juice plus inulin had significantly increased the survival cells in the gastric-bile environment. This treatment condition also significantly enhanced the growth of colon lactobacilli and benificial bifidobacteria after fermenting for 24 h but suppressed the growth of harmful microbes including fecal coliforms, clostridia and total anaerobic bacteria. Moreover, this specific treatment also stimulated significant increase of total short chain fatty acids (SCFA) in the colon section. Among all SCFA, acetate was the predominant metabolic product followed by propionate and butyrate respectively ©All Rights Reserved.